2005
DOI: 10.1002/cyto.b.20058
|View full text |Cite
|
Sign up to set email alerts
|

Impact of immunological platelet counting (by the platelet/RBC ratio) on haematological practice

Abstract: With the increasing availability of flow cytometers within haematology laboratories, a number of different groups began to investigate the applicability of this technology to accurately enumerate platelets and other cells within whole blood, with the ultimate aim of replacing manual counting reference methods. Six years ago, different candidate flow cytometric immunological platelet counting procedures were reviewed by the International Council for Standardisation in Haematology (ICSH) expert panel on cytometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
12
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
3
12
0
1
Order By: Relevance
“…This method measures the platelet count based on platelet/ RBC ratio and total RBC count. This method has been found to be very accurate [13] . But the procedure involves the detection of fluorescent labeled platelets in a fluorescence flow-cytometer which cannot be performed routinely in developing countries due to the costs involved.…”
Section: Discussionmentioning
confidence: 93%
“…This method measures the platelet count based on platelet/ RBC ratio and total RBC count. This method has been found to be very accurate [13] . But the procedure involves the detection of fluorescent labeled platelets in a fluorescence flow-cytometer which cannot be performed routinely in developing countries due to the costs involved.…”
Section: Discussionmentioning
confidence: 93%
“…Various authors have demonstrated excellent precision and accuracy of this method, as well as excellent correlation with the ICSH dual‐color immunofluorescence method . It is possibly even more precise than the reference method . For now, this method is the only immunologic PLT method available for routine use.…”
mentioning
confidence: 86%
“…A fully automated modification of this immunoplatelet method using CD61 antibodies is available in the Abbott CELL‐DYN Sapphire analyzer . Various authors have demonstrated excellent precision and accuracy of this method, as well as excellent correlation with the ICSH dual‐color immunofluorescence method . It is possibly even more precise than the reference method .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In questo ambito la citofluorimetria rappresenta l'esame di riferimento, ma per costi elevati e complessità analitiche non è ancora utilizzata nelle routine estese [3].…”
unclassified